Painting as model - Bois, Yve-Alain (Cambridge, Mass. : MIT Press, 1993)
Introduction: Resisting blackmail -- I. Totems of modernity: Matisse and "Arche-drawing" -- Kahnweiler's lesson -- II. Abstraction I: The De Stijl idea -- Strzemiński and Kobro: in search of motivation -- Piet Mondrian, New York City -- III. Abstraction II: Perceiving Newman -- Ryman's tact -- IV. Archaeology: Painting : the task of mourning -- Painting as model.
Includes bibliographical references (p. [259]-317) and index.
boek